Purpose and Policy in the Global Community - Russett, B. (Advances in Foreign Policy Analysis, 2006)
Few topics are as important in the study of international relations as the causes of wealth and poverty, and their interaction with militarization. Few scholars have contributed more to understanding these issues than Bruce Russett. Here Russett shows the linkages between wealth and conflict both substantively and temporally.